Deforestation and predator species richness as potential environmental drivers for roadkill of wild water deer in South Korea - Islam, Obaidul; Matsuyama, Ryota; Min, Kyung-Duk (Frontiers in Veterinary Science, 2025)
IntroductionThe roadkill incidence of Korean water deer (Hydropotes inermis argyropus) has become a nationwide concern in recent years because of its contribution to biodiversity loss. Various environmental risk factors for the occurrence of roadkill events were found. However, there is a gap in observational studies focusing on the effects of deforestation and predator species richness on the roadkill, despite their plausible mechanisms. This study aimed to investigate the associations between water deer roadkill events and environmental risk factors in South Korea.MethodsWe analyzed 1,986 roadkill events of water deer recorded on highway routes managed by the Korean National Transport Center from 2019 to 2021 as an outcome variable, and the values of environmental factors collated as explanatory variables. Multivariate logistic regression models were used to investigate these associations.ResultsThis study highlighted two main explanatory variables: predator species richness and deforestation, and the results indicate that higher deforestation level was associated with higher odds of the roadkill incidence, with an odds ratio of 1.15 [95% confidence interval (CI) = 1.07–1.25] from the ordinary model and 1.11 (95% credible interval = 1.03–1.21) from the spatial regression model. Conversely, predator species richness is negatively associated with the roadkill events, with an odds ratio of 0.75 (95% confidence interval = 0.69 to 0.80) from the ordinary regression model and 0.76 (95% credible interval = 0.66–0.86) from the spatial regression model.ConclusionThese findings suggest that conservational effort, such as preventing wildlife diversity and mitigating deforestation could reduce the incidence of water deer roadkill events.